(untitled) (La Aljaba. Segunda Época. Revista de Estudios de la Mujer, 2017)
There is a substantial corpus of literature that realizes the importance, in theoretical and methodological terms, to include social and community organizations (CSOs) in the various forms of welfare provision and social care delivery. Also, in Latin America, a prolific academic production -gender studies and / or feminist approaches- that has put the issue of the provision of care in contexts of poverty and inequality in the center of analysis, and debate. However, less attention has been paid to the change that occurred in the CSOS in relation to to their participation in the provision of care and to the place that women have played in these processes. In this regard, the article -based on the analysis of primary and secondary data- proposes approximate answers to the following questions: Which factors can explain the emergence of new CSOs and / or the reconfiguration of the existing ones in the provision of care? Is this a result of the weight of social welfare policies implemented from the nineties? Is it more a result of the transformation of the relations established at local level? Which is the place of women´s practices and subjectivities in these processes?